2005
DOI: 10.1073/pnas.0502589102
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary cycles of cooperation and defection

Abstract: The main obstacle for the evolution of cooperation is that natural selection favors defection in most settings. In the repeated prisoner's dilemma, two individuals interact several times, and, in each round, they have a choice between cooperation and defection. We analyze the evolutionary dynamics of three simple strategies for the repeated prisoner's dilemma: always defect (ALLD), always cooperate (ALLC), and tit-for-tat (TFT). We study mutationselection dynamics in finite populations. Despite ALLD being the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
352
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 333 publications
(366 citation statements)
references
References 29 publications
14
352
0
Order By: Relevance
“…Although TF2T was proposed as a remedy to avoid the inefficiency of TFT, its predictability opens another possibility of being exploited. Generous TFT avoids this dilemma between generosity and exploitability by introducing randomness in forgiving the co-player's defection [10,11,12,13]. However, its unpredictability might be a double-edged sword when it comes to public policy making, in which such random factors are not popular ideas [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although TF2T was proposed as a remedy to avoid the inefficiency of TFT, its predictability opens another possibility of being exploited. Generous TFT avoids this dilemma between generosity and exploitability by introducing randomness in forgiving the co-player's defection [10,11,12,13]. However, its unpredictability might be a double-edged sword when it comes to public policy making, in which such random factors are not popular ideas [14].…”
Section: Introductionmentioning
confidence: 99%
“…All these difficulties are rooted in the error vulnerability of TFT. Worse is that this is not the only weakness: A TFT population is invaded via neutral drift by unconditional cooperators (AllC), which, in turn, opens the back door to AllD [11,12,13,19]. It would thus be desirable if some modification overcame these shortcomings while preserving the strengths of TFT.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the game-theoretic model in this paper and some previous studies are 2×2 games, in which the cooperative dilemma has not been removed. But recent studies revealed that cooperative dilemma will vanish when a third strategy is introduced (Imhof et al, 2005). It shows that the three strategies form cycle which is similar to the "rock-paper-scissors" game.…”
Section: Resultsmentioning
confidence: 99%
“…In the following, the evolutionary dynamics of three repeated strategies ALLD, TFT and ALLC (Nowak and Sigmund, 1989;Imhof et al, 2005) on a graph with the influence of external force are also examined. The following payoff matrix with only one parameter, bð1 ob o 2Þ (Nowak and May, 1992), will be used:…”
Section: Updating An a Playermentioning
confidence: 99%